Development and validation of the Brief‐Mentalized Affectivity Scale: Evidence from cross‐sectional online data and an urban community‐based mental health clinic. Issue 11 (14th July 2021) - Greenberg, David M.; Rudenstine, Sasha; Alaluf, Rozita; Jurist, Elliot L.
Abstract: Objective: To develop and validate the Brief‐Mentalized Affectivity scale (B‐MAS), a shorter version of the Mentalized Affectivity Scale (MAS). Methods: In Study 1 ( N = 978), participants from Amazon's Mechanical Turk were administered a battery of questionnaires including the B‐MAS and traditional emotion regulation measures. In Study 2 ( N = 230), clients from a community clinic completed a separate battery of measures, including the B‐MAS, and personality and emotion regulation measures. Results: There were four main findings: (1) the B‐MAS is a psychometrically robust measure of emotion regulation and mentalization; (2) scores on the B‐MAS are highly predictive of many clinical diagnoses; (3) scores on the B‐MAS are just as or more predictive of wellbeing than traditional emotional regulation measures; and (4) as observed in an urban clinic with a diverse population, the B‐MAS is useful clinically, especially because of its brevity. Conclusion: The B‐MAS contributes to the expanding scope of research on emotion regulation and has valuable clinical applications.